Comprehensive analysis of peripheral T-cell and natural killer/T-cell lymphoma in Asian patients: A multinational, multicenter, prospective registry study in Asia - Sang Eun Yoon; Yuqin Song; Seok Jin Kim; Dok Hyun Yoon; Tsai-Yun Chen; Youngil Koh; Ka Won Kang; Ho Sup Lee; Kevin Kuang Wei Tay; Soon Thye Lim; Michele Poon; Cosphiadi Irawan; et al. (Elsevier, 2021)
Background: Peripheral T-cell lymphomas (PTCLs) are uncommon and their frequency is regionally heterogeneous. Several studies have been conducted to evaluate the clinical features and treatment outcomes of this disease entity, but the majority of these were conducted in limited areas, making it difficult to comprehensively analyze their relative frequency and clinical features. Furthermore, no consensus treatment for PTCLs has been established. Therefore, we conducted an Asia-specific study to understand the relative frequency of PTCLs and assess treatments and their outcomes in Asian patients. Methods: We performed a multinational, multicenter, prospective registry of adult patients with PTCLs that was named as the International Cooperative non-Hodgkin T-cell lymphoma prospective registry study where thirty-two institutes from six Asian countries and territories (Korea, China, Taiwan, Singapore, Malaysia, and Indonesia) participated. Findings: A total of 486 patients were registered between April 2016 and February 2019, and more than a half of patients (57%) had stage III or IV. Extranodal natural killer (NK)/T- cell lymphoma was the most common subtype (n = 139,28.6%), followed by angioimmunoblastic T-cell lymphoma (AITL, n = 120,24.7%), PTCL-not otherwise specified (PTCL-NOS, n = 101,20.8%), ALK-positive anaplastic large cell lymphoma (ALCL, n = 34,6.9%), and ALK-negative ALCL (n = 30,6.2%). The median progression-free survival (PFS) and overall survival (OS) were 21.1 months (95% CI,10.6-31.6) and 83.6 months (95% CI, 56.7-110.5), respectively. Upfront use of combined treatment with chemotherapy and radiotherapy showed better PFS than chemotherapy alone in localized ENKTL whereas consolidation with upfront autologous stem cell transplantation (SCT) provided longer PFS in advance stage ENKTL. In patients with PTCLs other than ENKTL, anthracycline-containing chemotherapies were widely used, but the outcome of those regimens was not satisfactory, and upfront autologous SCT was not significantly associated with survival benefit, either. The treatment outcome of salvage chemotherapy was disappointing, and none of the salvage strategies showed superiority to one another. Interpretation: This multinational, multicenter study identified the relative frequency of each subtype of PTCLs across Asian countries, and the survival outcomes according to the therapeutic strategies currently used. Funding: Samsung Biomedical Research Institute